Students perceptions of service quality in the open and distance learning institution - Md Zabid, Abdul Rashid; Hairuddin , Harun (Open University Malaysia (OUM), 2005)
The Malaysian economy experienced an economic boom in the mid-1990s. At the same time, the demand for higher education increased tremendously. In 2005, there were more than 18 public universities and 27 private universities and university colleges in Malaysia and more than 500 private colleges offering a variety of courses ranging from the certificate level to the degree level. Some of these institutions offered their own diplomas or degrees and others work in collaboration with local or foreign colleges and universities.